FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU MAHASISWA DALAM MEMILIH JURUSAN PADA FAKULTAS EKONOMI UNISKA - Prihatini Ade Mayvita; Erni Alfisah; Rizqi Elmuna Hidayah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
Colleges are expected to continue to be able to improve their quality through repair or renewal. One of the reforms can be done by granting autonomy to universities. Given the autonomy of universities is expected to be able to manage and carry out repairs. Another the impact of the granting of autonomy that is the increasing number of private colleges have sprung up recently, which resulted in triggering competition among the private universities in gaining prospective students. For customers that prospective students with a number of private colleges will give you many choices for them to determine the college considered the best quality. The purpose of this research is to analyze the influence of individual characteristics, marketing mix, psychological variables, organization, and leadership on student's decision choosing economics faculty Uniska MAB non-regular classes. The analysis technique used is multiple linear regression hypothesis testing through simultaneous significance test (test F), partial significance test (t test) and test the coefficient of determination (R ² test). The results showed that simultaneous variable individual characteristics (X1), services marketing mix variables (X2), psychological variables (X3), organizational variables (X4), leadership variable (X5) has no significant effect on student's decision (Y). Partial Partial that the variables that significantly is variable organization while variable individual characteristics, marketing mix variables, psychological variables, as well as leadership variable effect is not significant.